The essential carer's guide - Jordan, Mary (Hammersmith Press, 2006)
Illustrated with individual case stories, this book covers physical, social, and financial needs, across the stages of immediate, intermediate and advanced care. It is useful as a practical companion for those caring for, or responsible for the care of, an elderly friend or relative.